A Novel CD34-Specific T-Cell Engager Efficiently Depletes Stem Cells and Acute Myeloid Leukemia Cells in Vitro and In Vivo - Arruda, Lucas C M; Jin, Liqing; Lambert, Melanie; Sanchez Rivera, Laura; Alvez, Renato; Rocha de Moura, Tales; Mim, Carsten; Axelsson-Robertson, Rebecca; Dick, John E.; Mattsson, Jonas; Onfelt, Bjorn; Carlsten, Mattias; et al. (Blood, 2021)
ASH Abstract. Intro Acute myeloid leukemia (AML) and high-risk myelodysplastic syndromes (MDS) are poor prognosis hematological malignancies characterized by abnormal hematopoiesis and dysfunctions of the hematopoietic stem cell system. Chemotherapy remains the standard of care but is associated with side effects and often high rates of relapse. Today, less than a third of patients diagnosed with AML are cured. Bispecific T-cell engagers (BiTEs) are promising immunotherapeutic agents intended for cancer treatment. BiTEs are small molecules constructed of two single chain variable fragments (scFv) connected in tandem by a flexible linker that acts by retargeting T-cells against tumor cells. One scFv binds to CD3, while the second scFv binds to a tumor-associated antigen. This structure and specificity allow a BiTE construct to physically link a T-cell to a tumor cell, stimulating effector cell activation ultimately leading to cytokine production and tumor killing. Material BiTEs against CD34/CD3 and relevant controls were constructed by recombinant DNA technology and purified from the supernatants of transfected CHO cells following standard procedures. The scFv domain binding to CD34 is positioned N-terminally, and the scFv binding to CD3e C-terminally followed by a hexa-histidine sequence. Results By co-culturing T-cells and target AML cells for 48 h in the presence of increasing concentrations of BiTE or controls, we observed that CD34-BiTE efficiently triggered T-cell-mediated depletion of the CD34 hi and CD34 low cell lines, while negative controls killed none of the target cell lines. Next, we examined the T-cell activation and proliferation. We observed that both CD4+ and CD8+ T-cells presented high levels of CD25/CD69 expressions when the CD34+ cell lines were co-cultured with T-cells in the presence of the CD34/CD3 BiTE. No unspecific activation was found when CD34- cell line was used as target cell. Since CD34 is constitutively expressed by HSCs, the CD34-specific BiTE may deplete not only CD34 +AML blasts but also healthy HSCs. To test this, T-cells and HSCs were purified from PBSC grafts and co-cultured in the presence of either CD34/CD3 BiTE or controls. After co-culture, a significant depletion of CD34 + HSCs was observed for the CD34/CD3 BiTE. To address the potential of the anti-CD34 BiTE in vivo, we next established a human CD34 + cell line in NSG mice per intravenous injection and randomized into three different groups and started treatment the day after. Two groups of mice received two consecutive cycles of one intraperitoneal injection of freshly isolated human T-cells followed by daily intravenous injections of either BiTE or control. The mice were euthanatized at day 21 by which the AML burden was measured, and T-cells quantified. No side effects of the treatment, including after BiTE administration, was observed. There were statistically significant reductions of leukemia burden in both bone marrow and spleen in mice receiving T-cells and BiTE compared to T-cells only and control. Conclusions We show that the CD34/CD3 BiTE is able to promote T-cell activation and killing of CD34-expressing target cells with high efficacy in vitro and in vivo, supporting the translation of this drug into clinical trials. In this scenario, the treatment with CD34-targeting BiTE prior to HSCT would trigger the patient's T-cells to deplete CD34 + leukemic blasts and HSCs. As consequence, this adjuvant treatment would decrease the use of cytotoxic and cytostatic conditioning drugs before HSCT, reducing life-threatening complications such as GvHD and infections. Arruda: Anocca: Current Employment, Research Funding. Dick: Celgene, Trillium Therapeutics: Membership on an entity's Board of Directors or advisory committees, Research Funding. Mattsson: MattssonAB medical: Current Employment, Current holder of individual stocks in a privately-held company. Onfelt: Desumo: Current Employment, Current holder of individual stocks in a privately-held company. Uhlin: XNK therapeutics: Current Employment, Current holder of stock options in a privately-held company.